Reverse takeovers : motivations, risks & returns. An investigation on value creation through reverse takeovers. - Chew, Hew Hui. (2008)
This study aims to achieve the following objectives: 1) Understand and document in detail the process and requirements of an RTO through individual case studies of actual RTOs which have taken place in Singapore 2) Investigate the broader, as well as specific, motivations and reasons of undertaking an RTO through the perspectives of both the public-listed shell company (“shell company”) and the private firm 3) Examine the stock prices and returns of the shell company a period before and after the RTO’s first public announcement, with the aim of looking at how the announcement affects the stock prices and returns